Sr 2 MnO 2 Na 1.6 Se 2: A Metamagnetic Layered Oxychalcogenide Synthesized by Reductive Na Intercalation to Break [Se 2 ] 2– Perselenide Dimer Units - Giri, S; Dey, S; Suard, E; Clarke, SJ (American Chemical Society, 2024)
Recent advances in anion-redox topochemistry have enabled the synthesis of metastable mixed-anion solids. Synthesis of the new transition metal oxychalcogenide Sr2MnO2Na1.6Se2 by topochemical Na intercalation into Sr2MnO2Se2 is reported here. Na intercalation is enabled by the redox activity of [Se2]2– perselenide dimers, where the Se–Se bonds are cleaved and a [Na2–x Se2](2+x)– antifluorite layer is formed. Freshly prepared samples have 16(1) % Na-site vacancies corresponding to a formal oxidation state of Mn of +2.32, a mixed-valence between Mn2+ (d5) and Mn3+ (d4). Samples are highly prone to deintercalation of Na, and over two years, even in an argon glovebox environment, the Na content decreased by 4(1) %, leading to slight oxidation of Mn and a significantly increased long-range ordered moment on the Mn site as measured using neutron powder diffraction. The magnetic structure derived from neutron powder diffraction at 5 K reveals that the compound orders magnetically with ferromagnetic MnO2 sheets coupled antiferromagnetically. The aged sample shows a metamagnetic transition from bulk antiferromagnetic to ferromagnetic behavior in an applied magnetic field of 2 T, in contrast to the Cu analogue, Sr2MnO2Cu1.55Se2, where there is only a hint that such a transition may occur at fields exceeding 7 T. This is presumably due to the higher ionic character of [Na2–x Se2](2+x)– layers compared to [Cu2–x Se2](2+x)– layers, reducing the strength of the antiferromagnetic interactions between MnO2 sheets. Electrochemical Na intercalation into Sr2MnO2Se2 leads to the formation of multiphase sodiated products. The work shows the potential of anion redox to yield novel compounds with intriguing physical properties.